2021
DOI: 10.1186/s13054-020-03452-x
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine in acute phase of severe traumatic brain injury “an old drug for new uses?”

Abstract: Maintaining an adequate level of sedation and analgesia plays a key role in the management of traumatic brain injury (TBI). To date, it is unclear which drug or combination of drugs is most effective in achieving these goals. Ketamine is an agent with attractive pharmacological and pharmacokinetics characteristics. Current evidence shows that ketamine does not increase and may instead decrease intracranial pressure, and its safety profile makes it a reliable tool in the prehospital environment. In this point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 52 publications
0
25
0
2
Order By: Relevance
“…Therefore, the intracranial pressure-raising effect of ketamine was allowed during spontaneous breathing in the cesarean section patients included in our study. Furthermore, although other studies have suggested that ketamine may cause a decrease in intracranial pressure [ 37 , 38 ] or have no significant effect on intracranial pressure [ 36 , 39 , 40 ], the prevailing view remains that ketamine has an increased effect on intracranial pressure. However, it is unclear whether this increase in intracranial pressure is sustained and whether it has associated adverse effects in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the intracranial pressure-raising effect of ketamine was allowed during spontaneous breathing in the cesarean section patients included in our study. Furthermore, although other studies have suggested that ketamine may cause a decrease in intracranial pressure [ 37 , 38 ] or have no significant effect on intracranial pressure [ 36 , 39 , 40 ], the prevailing view remains that ketamine has an increased effect on intracranial pressure. However, it is unclear whether this increase in intracranial pressure is sustained and whether it has associated adverse effects in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Though these are a novel class of drugs deserving close study, more data are necessary to prove their efficacy for treatment of brain injury, as historically many compounds have seemed promising in vitro , including likely hundreds of compounds thought to facilitate neuroplasticity and neuroprotection, but have not borne out in clinical trials ( 61 , 62 ). There is already mixed evidence to suggest the use of non-classical psychedelics ketamine ( 63 , 64 ), as well as tetrahydrocannabinol (THC) ( 65 , 66 ) and cannabidiol ( 67 , 68 ), as neuroprotectants after TBI and stroke. Presence of THC on urine drug screen is associated with decreased mortality in adult patients sustaining TBI ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many of these studies reported no change in ICP in healthy individuals and did not report concurrent changes in mean arterial pressure and calculated cerebral perfusion pressure 48 . As such, current opinions consider the rise in ICP caused by ketamine to be a myth 33,56,57 . In fact, in more recent preclinical trials modeling increases in ICP, racemic ketamine (10 mg/kg) was shown to decrease ICP by a maximum of 10.8% 58 .…”
Section: Discussionmentioning
confidence: 99%